The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1002/art.22015
|View full text |Cite
|
Sign up to set email alerts
|

Association of α‐actinin–binding anti–double‐stranded DNA antibodies with lupus nephritis

Abstract: Objective. Anti-double-stranded DNA (antidsDNA) antibodies may contribute to the pathogenesis of glomerulonephritis (GN) by cross-reacting with ␣-actinin in murine models and in some patients with systemic lupus erythematosus (SLE). We therefore sought to determine possible disease associations with serologic and clinical features and to characterize this new autoantibody specificity.Methods. One hundred patients with SLE were recruited into this multicenter study, as well as 100 rheumatic disease controls and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
36
2
7

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 46 publications
(51 reference statements)
6
36
2
7
Order By: Relevance
“…Notably, Ig eluted from kidneys of nephritic lupus mice bound to ␣-actinin, further supporting the notion that ␣-actinin is a target for pathogenic lupus autoantibodies (4). Recent human studies have shown that high titers of anti-␣-actinin Abs were detected at an early stage of lupus nephritis and that anti-␣-actinin Abs are significantly associated with glomerulonephritis in lupus patients (5)(6)(7). These latter findings suggest that anti-␣-actinin Abs may be useful as a serological marker in human lupus nephritis.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…Notably, Ig eluted from kidneys of nephritic lupus mice bound to ␣-actinin, further supporting the notion that ␣-actinin is a target for pathogenic lupus autoantibodies (4). Recent human studies have shown that high titers of anti-␣-actinin Abs were detected at an early stage of lupus nephritis and that anti-␣-actinin Abs are significantly associated with glomerulonephritis in lupus patients (5)(6)(7). These latter findings suggest that anti-␣-actinin Abs may be useful as a serological marker in human lupus nephritis.…”
supporting
confidence: 56%
“…Furthermore, all the common peptide sequences from each respective Ag were in B cell epitope regions as determined by Bcepred, a B cell epitope prediction program (22). Importantly, the common peptide sequence from ␣-actinin is found in its actin binding domain, a region recently determined to be targeted by the anti-␣-actinin response in human lupus nephritis (5).…”
Section: Ags Bound By Sera From ␣-Actinin-immunized Mice Share a Commmentioning
confidence: 99%
“…46 The list includes antidsDNA, antihistones, 47-52 and antibodies versus endogenous antigens, such as antiactinin. 10,13,53,54 Actually, definition of specific renal and serum levels of the above antibodies are in progress and will be reported very soon (G.M. Ghiggeri, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12] They consider a pre-eminent role of circulating anti-double stranded DNA (dsDNA) antibodies that they can interact, for mimicry, with glomerular antigens expressed at the cell surface of podocytes and mesangial cells 7,[13][14][15] or in the glomerular basement membrane. 12,[16][17][18][19][20] Chromatin and nucleosomes deriving from ineffective fragmentation may interact with negatively charged constituents of the basement membrane 7,16 and become the planted antigen for anti-dsDNA (and autoantibodies of other specificities).…”
mentioning
confidence: 99%
See 1 more Smart Citation